Pesticide residues in cow's milk - Ćosić, Milivoje (Array, 2021)
Quality of milk plays a key role in its wide consumption but also of its involvement in a large series of derived products, such as yogurt, cheese, butter, and ice cream. An effective LC-MS/MS method has been validated for the determination of 81 different pesticide residues in milk samples. The analyses comprised 44 milk samples collected during 2019. From all inspected pesticides, only metalaxyl (present in 11.36 % samples), bifenthrin and metolachlor (9.09 %), dimethoate (4.55 %), prochloraz and thiacloprid were detected in 2.27 % of analysed samples. The detections of trifloxystrobin and bifenthrin were above the maximum residue levels (MRLs). The Commission Regulation (EU) 2017/1135 standardizes the MRLs for dimethoate and omethoate in certain products, but a MRL for dimethoate residues in milk has not been established jet. All the other pesticide detections were below the MRLs.